Evolution of Choroidal Neovascularization due to Presumed Ocular Histoplasmosis Syndrome on Multimodal Imaging including Optical Coherence Tomography Angiography - T. Y. Alvin Liu; Alice Yang Zhang; Adam Wenick (Case Reports in Ophthalmological Medicine)
A 37-year-old Caucasian woman presented with acute decrease in central vision in her right eye and was found to have subfoveal choroidal neovascularization (CNV) due to presumed ocular histoplasmosis syndrome (POHS). Her visual acuity improved from 20/70 to 20/20 at her 6-month follow-up, after 3 consecutive monthly intravitreal bevacizumab injections were initiated at her first visit. Although no CNV activity was seen on fluorescein angiography (FA) or spectral-domain optical coherence tomography (SD-OCT) at her 2-month, 4-month, and 6-month follow-up visits, persistent flow in the CNV lesion was detected on optical coherence tomography angiography (OCTA). OCTA shows persistent vascular flow as well as changes in vascular flow in CNV lesions associated with POHS, indicating the continued presence of patent vessels and changes in these CNV lesions, even when traditional imaging of the lesion with OCT and FA indicates stability of the lesion with no disease activity. Additional cases with longitudinal follow-up are needed to assess how OCTA should be incorporated into clinical practice.